Verified software : theories, tools, and experiments : 8th International Conference, VSTTE 2016, Toronto, ON, Canada, July 17-18, 2016, Revised selected papers /: theories, tools, and experiments : 8th International Conference, VSTTE 2016, Toronto, ON, Canada, July 17-18, 2016, Revised selected papers. (2016) - Unknown
No abstract available